KETERKAITAN DETERMINAN ADOPSI TEKNOLOGI DENGAN KETERTARIKAN PELAKU USAHA PENGOLAHAN IKAN MENGGUNAKAN DIGITAL MARKETING - Rifki Muhamad Imadudin; Elmira Syahdanabila Rozak; Ferdiansyah; Zulfikar Noormansyah; Rudi Priyadi; Rina Nuryati (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2026)
The advancement of digital technology opens opportunities for market expansion for business actors; however, the utilization of digital marketing in fish processing enterprises remains suboptimal. This study aims to examine the relationship between seven determinants of technology adoption—Knowledge (X1), Perceived Ease of Use (X2), Trust (X3), Perceived Usefulness (X4), Relative Advantage (X5), Perceived Risk (X6), and Technology Access (X7)—and the intention of fish processing entrepreneurs to implement digital marketing technology. Data collection was conducted using a total sampling method involving all 35 members of the Fishery Product Processing and Marketing Group (Poklahsar) in Tasikmalaya City. Spearman's Rank Correlation was employed as the analytical method appropriate for ordinal-scale data. The results indicate a strong positive correlation with a coefficient of ρ = 0.776, and a t-statistic of 7.064, which exceeds the t-table value of 2.034 at α = 0.05, thereby rejecting the null hypothesis (H₀) with p < 0.001. These findings demonstrate that more favorable determinant factors correspond to a higher intention among business actors to adopt digital marketing. The research implications emphasize the importance of integrated intervention programs that encompass enhancing digital literacy, strengthening trust in digital platforms, and expanding technology accessibility for fishery business actors.